Relationship Between Distributive Justice, Ethical Leadership, and Turnover Intention with the Mediating Effects of Ethical Climate - Mehmood, Nasir; Ungku Norulkamar, Dr; Sobia Irum, Dr (International Journal of Engineering and Technology, 2018)
Leaders form an organizationâ€™s ethical climate and influence employeesâ€™ perceptions and intentions. Employeesâ€™ intentions become positive when leaderâ€™s personal ethics and ethical climate are congruent. The current study focused on the relationships among ethical leadership, distributive justice and ethical climate in the formation of employeeâ€™s turnover intention. The purpose of the study is (1) to examine whether leaderâ€™s ethics significantly impact over turnover intention, (2) to what extent distributive justice effects turnover intention, and (3) to determine the indirect impact of ethical leadership on turnover intention through ethical climate. The valid sample data was randomly collected through structured questionnaire distributed among 265 employees from 9 different banks located in Northern Punjab region of Pakistan. Structural equation modeling (SEM) was used for data analysis using AMOS 22.0. Results revealed that distributive justice is significantly related to turnover intentions and ethical climate mediated between ethical leadership and turnover intention. This study contributes to the existing literature by considering both, distributive justice and ethical leadership in predicting turnover intention. When enacting policies and procedures, leaders should set ethical and justice tone that can be helpful to facilitate ethical behavior and also minimize turnover intentions among employeeÂ